Studi Pengaruh Kontaminasi Properti Rheology Water Based Mud di Lapangan Sunyu - Abdullah Rizky Agusman (Fakultas Teknik Universitas Bhayangkara Jakarta Raya, 2022)
This project focuses on Investigation of effect of contaminants on the Rheological Properties of Water-based Drilling Mud. For any drilling operation to be termed successful, care must be taken during the selection and application of the drilling fluid which are key factors that should be considered. Any actions contrary to carefully selection and application of drilling fluids could have very dire consequences. Based on the experiment work done on water base mud system to ascertain the effect of contaminants (salt, silica sand, cement and carbonate) on the rheological properties and performance of the mud, it shows that the presence of a contaminant on the drilling mud either reduces or increases the rheological properties of the mud system and in turn affects the rate of penetration, it performance and also poses serious drilling problems. It was observed that the presence of Sodium salt in the mud system increased the fluid loss into the formation. It was further observed that while Apparent Viscosity, Gel Strength increases as the mass increase from 1g to 5g, the pH and Plastic Viscosity almost did not change. The Yield point increases little. With Cement as contaminant, it shows all rheological properties of the mud increased markedly, as the quantity of the cement used is increased from 1g to 5g and the pH does not change. Silica contamination has not showed any marked effect on the nature of the drilling mud. In fact, the more the amount of the contaminant (Silica) is added, the closer it properties are to the blank sample that do not have contaminants. The carbonate effect is largely on the Gel strength which decreases as the amount of added carbonate increases. The pH has no charges, which also means carbonate keeps the mud in it alkaline state, as it was the case with cement.